Influence of community dialogues on social accountability in the health system in Nairobi County, Kenya - Abuga, Malkia M.; Tenambergen, Wanja M.; Njoroge, Kezia M. (International Journal Of Community Medicine And Public Health, 2022)
Background: Social accountability encompasses a variety of strategies that enable citizens to express their concerns about the performance of health-care services. Community dialogues provide a forum for community engagement and participation in the health care system. However, there is little documentation on how it is used to improve social accountability within government community health structures. The purpose of this study was to determine the influence of community dialogues on social accountability in Nairobi County, Kenya. Methods: A qualitative study was conducted that included in-depth interviews with key stakeholders purposively selected. A total of three focus group discussions with 23 participants, eight key informant interviews and document review of minutes were conducted. Data analysis was done using thematic analysis. Results: Findings showed that community dialogues were held quarterly. The forums were mostly used for education purposes with little evidence on community engagement. Minutes showed what the community health assistant and community health volunteer said to the community with minimal input from the community members. Feedback was a challenge because the health management team hardly attended community dialogues due to logistic and workload issues. Conclusions: There is need of practical strengthening community dialogues through use of tools like chalk board and community scorecard as advocated in the community health policy. However, in practice, these tools were hardly used resulting to missed opportunity for the community to voice their opinions on health services.